PENINGKATAN KONDISI FISIK DOMINAN ATLET GULAT KABUPATEN NGANJUK KATEGORI JUNIOR USIA 17-20 TAHUN MELALUI PROGRAM LATIHAN SIRKUIT - Ayuna Falum Luksita; Tatok Sugiarto; Surya Adi Saputra (Jayabama: Jurnal Peminat Olahraga, 2024)
For an athlete who is in good physical condition is a unified component that must be possessed both when practicing and competing, this also applies to wrestling athletes. The problem in this research is that there is a decrease in the physical condition experienced by wrestling athletes in Nganjuk Regency, especially in the Junior category aged (17-20 years). The dominant physical condition of wrestling consists of the physical components of arm power, leg power, flexibility, balance, speed and endurance. The purpose of this research is to improve the dominant physical condition of Nganjuk wrestling athletes by providing a circuit training program. The research design used is Sports Action Research (PTO). This research uses a type of qualitative research which is carried out in 2 cycles, in which each cycle consists of 5-6 meetings. The implementation took place in the Hall of Patianrowo 1 Public Middle School which is located on Jalan Raya Ngepung, Sukorejo Village, Patianrowo District, as a training ground for wrestling athletes, Nganjuk Regency. The results of this study stated that all 6 components of the dominant physical condition tested had succeeded in meeting the success criteria, namely the components of arm power by 83.33%, leg power by 75%, flexibility by 91.67%, balance by 100%, speed of 83.33%, and durability of 83.33%. This shows that the aim of the researchers to improve the physical condition of junior wrestling athletes in Nganjuk district has been achieved so that the research can be completed until cycle II.